The Effects of Plant Growth Regulators from Endophytic Bacteria on Propagation of Rare and Economically Valuable Plants (Zingiberaceae) by Plant Tissue Culture Technique - Khotchanalekha, Kulwadee; Triped, Janjira; Chaipukdee, Nattapong (Srinakharinwirot University Journal of Sciences and Technology, 2025)
The purposes of this study were to investigate rare and economically valuable plants (Zingiberaceae) in Chaiyaphum Province and to expand their population by using tissue culture technique. The study's findings demonstrated that ginger plants could be gathered from the regions covered by the herb group community enterprises in the province of Chaiyaphum, which included Ban Tha Thang Kwian and the Thai Way Ban Sai Ngam. These two groupings are sources that plant for agricultural cultivation and gather species for conservation. It was found that a total of 4 genera and 8 species of ginger plants were planted and collected, such as ginger (Zingiber officinale Roscoe), Pyle (Zingiber cassumunar Roxb), Galangal (Alpinia galanga (L.) Willd.), Chinese keys (Boesenbergia rotunda L. Mansf.), Turmeric (Curcuma longa L.), Mango ginger (Curcuma mangga Valeton and Zijp), Pathumma (Curcuma alismatifolia), and White Okra (Curcuma parviflora). An interesting plant, White Okra samples were surface sterilized before propagated through plant tissue culture. This was achieved by first sterilizing with 20% Clorox for 10 minutes and then sterilizing them again with 10% Clorox for 10 minutes, resulting in a 96% sterility rate for the plant samples. Additionally, the plant samples could increase the most in number at 2.5 shoots per tissue piece. When MS medium supplemented with TDZ in combination with IAA derived from endophytic bacteria was used in place of commercial NAA (1:0.1 mg/L), a 100% shoot induction rate was achieved, with the highest average number of shoots at 2.25 shoots per explant. Moreover, the medium containing only IAA (0.1 mg/L) from isolate ZCK-8 resulted in the highest average number of roots and root length per explant. The results of the experiment indicated that the IAA hormone from the ZCK-8 isolate could successfully stimulate the growth of plant samples' shoots and roots comparable to the commercial hormone NAA.